What drives domestic tourists' intention to stay at green hotels in West Java? Environmental attitude as a mediator - Indriana Damaianti; Siti Faizah Zainal (SAINTEKS : Jurnal Sain dan Teknik, 2026)
The rapid growth of hotels in West Java, a province with the largest number of accommodations, has raised environmental concerns due to resource consumption, waste generation, and pollution. In addition, room occupancy remains unstable, and the adoption of green hotels is still low, highlighting the need for strategies to address these ongoing challenges. This study aims to examine the factors influencing domestic tourists’ intention to stay at green hotels in West Java, with environmental attitude as a mediating variable. Data were collected from domestic tourists visiting West Java using a combination of convenience and purposive sampling. A total of 346 valid responses were analyzed using the PLS-SEM technique with SmartPLS 4.1.0.3. The findings indicate that green promotion and green perceived value positively influence environmental attitude. Only environmental attitude and green perceived value have a positive effect on the intention. In contrast, promotion does not directly affect the intention. Environmental attitude fully mediates the effect of promotion on the intention, and partially mediates the relationship between green perceived value and the intention to stay at green hotels in West Java. This study contributes to the Theory of Planned Behavior (TPB) by integrating green promotion and green perceived value to shape green consumer behavior and supports practical strategies to promote environmentally responsible consumer behavior, particularly among tourists. The limitation lies in the sample, which does not include international tourists.